Interactive mobile learning to improve computational thinking and achievement in digital systems courses - Anak Agung Gde Ekayana; Desak Made Dwi Utami Putra; I Gde Wawan Sudatha (Jurnal Inovasi Teknologi Pendidikan, 2025)
The digital era has fundamentally transformed classroom instructional approaches, shifting the focus from completing subject matter to meaningful student engagement and active knowledge construction. Grounded in constructivist learning theory and principles of computational thinking, this study aims to examine the effectiveness of interactive mobile learning as a technology-enhanced instructional innovation in digital systems education. The innovation integrates multimedia, interactivity, and problem-based activities to support students’ analytical and algorithmic reasoning. A quasi-experimental method was employed, involving 112 students enrolled in a digital systems course, with a nonequivalent control group pretest–posttest design. Data were analysed through multivariate analysis of covariance, independent T-tests, and N-gain analysis to evaluate learning effectiveness. The results revealed significant effects, both partial and simultaneous, with the experimental group consistently outperforming the control group. T-test findings indicated statistically significant differences between students using interactive mobile learning and those receiving conventional instruction. Furthermore, N-gain analysis showed improvements of 0.65 in computational thinking skills and 0.70 in learning achievement, categorised as medium to high gains. These findings confirm that interactive mobile learning effectively enhances learning outcomes. Therefore, it is recommended that educators integrate interactive mobile learning into digital systems instruction to foster students’ computational thinking and academic achievement.